2017 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2017
DOI: 10.1109/bibm.2017.8217839
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating automatic methods to extract patients' supplement use from clinical reports

Abstract: The widespread prevalence of dietary supplements has drawn extensive attention due to the safety and efficacy issue. Clinical notes document a great amount of detailed information on dietary supplement usage, thus providing a rich source for clinical research on supplement safety surveillance. Identification the use status of dietary supplements is one of the initial steps for the ultimate goal of the supplement safety surveillance. In this study, we built rule-based and machine learning-based classifiers to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Like the previous study [ 13 ], the sources of errors were mainly made up of three parts. First, there are new patterns we failed to generate from the training set.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Like the previous study [ 13 ], the sources of errors were mainly made up of three parts. First, there are new patterns we failed to generate from the training set.…”
Section: Discussionmentioning
confidence: 99%
“…The rule-based classifier was developed on the training data and further tested using the test data. Two of our previous studies [ 12 , 13 ] have shown that indicator words are extremely important in recognition and detection use status of dietary supplements. Based on the training data, a set of rules were generated using a variety of status indicators, which were compiled from reviewing the clinical notes and incorporated from other works identifying the use status of medications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations